Doppler ultrasound and 2D shear wave ultrasound elastography for liver fibrosis evaluation in Fontan-associated liver disease - Nakarin Inmutto; Attaporn Jantarangkoon; Natthapong Nimitrungtawee; Nattaporn Sriwicha; Sarawut Kongkarnka; Saviga Sethasathien; Tanop Srisuwan (BMC Gastroenterology)
Abstract Background The Fontan operation improves survival in patients with single ventricle physiology but is associated with Fontan-associated liver disease (FALD), characterized by progressive fibrosis due to prolonged elevated central venous pressure. While 2D shear wave elastography (2D-SWE) can assess fibrosis, it often overestimates stiffness in congestive conditions. Doppler ultrasound, which evaluates hepatic hemodynamics, may complement 2D-SWE for fibrosis assessment. This study evaluated the diagnostic performance of Doppler ultrasound and 2D-SWE in assessing hepatic fibrosis in Fontan patients and compared the findings with biopsy-proven fibrosis severity. Method A retrospective study was conducted on 27 Fontan patients who underwent Doppler ultrasound, 2D-SWE, and liver biopsy between January 2020 and December 2022. ROC curves and AUC values were used to assess diagnostic performance. Results AST to Platelet Ratio Index (APRI) and Fibrosis-4 index (FIB-4) scores demonstrated good discriminatory performance, with AUC values of 0.79 and 0.72, respectively. Resistive Index (RI) of hepatic artery showed moderate discriminatory performance (AUC = 0.62), while 2D-SWE demonstrated poor discriminatory ability (AUC = 0.35). When RI was combined with APRI, the AUC improved from 0.79 to 0.82. Conclusion APRI and FIB-4 provided the most accurate assessment of significant fibrosis, while RI of hepatic artery may serve as a useful adjunct to serum biomarkers. Incorporating Doppler ultrasound into a multi-parametric model may improve fibrosis evaluation in Fontan patients.